Phosphorus modifies the association between body mass index and uric acid: Results from NHANES 2007-2018. - Yue Chen; Jing Luo; Xiao-Man Ma; Xiang-Ping He; Wan-Lin Zhang; Shao-Yong Wu; Xiao-Chun Mo; Wei-Chao Huang; Xu-Guang Guo (PLoS ONE)
Introduction Studies in recent years have shown that high uric acid causes harm to the human body, which has become a serious public health problem. Elevated serum uric acid has been shown to be associated with obesity, but the relationship between BMI and uric acid (UA) remains controversial. Although the association between BMI and UA has been well studied, the effect of phosphorus levels in vivo on this association remains unclear. This study aimed to determine the relationship between BMI and serum uric acid and the effect of phosphorus on the relationship between the two. Research design and methods The present study analyzed data from the National Health and Nutrition Examination Survey (NHANES) continuous 2007-2018 cycle. We included 10786 participants aged 20 years and over. Multivariable linear regression was performed to assess the association between BMI and serum uric acid. phosphorus was stratified into low phosphorus (<3.3 mg/dl), middle phosphorus (3.3-3.9 mg/dl) and high phosphorus (>3.9 mg/dl). Correction of the effect of phosphorus was assessed by testing the interaction between BMI and UA in multivariate linear regression. Results In this cross-sectional study, we found that BMI was positively associated with UA in the female population but not significantly in the male population or in the total population. In multiple regression analysis, UA was 0.51 higher in the highest female BMI group than in the lowest group (p = 0.0001). The relationship between BMI and UA differed significantly by gender under the influence of phosphorus, with men and women in Model II having a greater elevation of UA in men than in women within most groups. (BMI >30, phosphorus >3.9 mg/dl, β:0.83 95% CI: 0.43, 1.23 vs β: 0.79 95% CI: 0.30, 1.29). In addition, phosphorus significantly altered the positive association between BMI and UA in most models. Conclusion Our results indicate significant associations between BMI and uric acid in women, with higher BMI values likely to be associated with a higher risk of hyperuricemia, suggesting that uric acid levels in obese people should be closely monitored in clinical practice. Phosphorus and BMI have an interactive effect in elevating UA and should be noted as indicators of phosphorus in clinical practice.